PERTANGGUNGJAWABAN PIDANA PEKERJA SEKS KOMERSIAL BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (STUDI KASUS: 516/PID.SUS/2017/PN.SMN - Donny David; Mety Rahmawati (Fakultas Hukum Universitas Tarumanagara, 2018)
The criminal liability issue of commercial sex workers is a hot issue among lawyers in Indonesia. Responsibility for criminal pimps has been positively regulated in legislation, but for commercial sex workers it certainly has not been explicit. That is the reason why this research is raised. The problem of this research is how criminal responsibility of commercial sex worker in prostitution crime through online media pursuant to Law Number 19 Year 2016 about amendment of Law Number 11 Year 2008 About Information and Electronic Transaction (Case Study: 516 / Pid. Sus / 2017 / PN Smn This research will be carried out using huku normati research method with case and law approach.The result of this research is that in Indonesia, criminal liability to commercial sex workers is not explicitly regulated, but implicitly regulated The legal umbrella that can be used to hold criminal liability for commercial sex workers is the Law on EIT, where if the commercial sex worker uses online media to prostitute herself, she may be held criminally liable.